Failure to block adhesion of Plasmodium falciparum-infected erythrocytes to ICAM-1 with soluble ICAM-1. - Craig, A G (1997)
The adhesion of Plasmodium falciparum-infected erythrocytes is thought to play a central role in the pathogenesis of severe malaria. ICAM-1 has been identified as one of the host receptors for parasitized erythrocytes and has been implicated as being involved in progression to cerebral malaria. Thus, intervention strategies based on the reversal of this interaction could potentially be used to reduce morbidity and mortality. We have investigated the inhibition of the interaction between ICAM-1 and infected erythrocytes by using recombinant soluble ICAM-1 as competitor and find that we are unable to reduce adhesion to ICAM-1 in vitro.